Family factors associated with adolescent self‐harm: a narrative review. Issue 2 (April 2016) - Fortune, Sarah; Cottrell, David; Fife, Sarah
Abstract : This narrative literature review focuses on family factors that might be amenable to intervention using family therapy (n=126). Domains of interest include parent/child interactions, inter‐parental relationships, child characteristics, parental characteristics, wider system factors, treatment needs and moderators. The focus of family‐orientated treatment with this population should focus on maximizing cohesion, attachment, adaptability, family support, parental warmth while reducing maltreatment, scapegoating and moderating parental control. Close working relationships with child protection services and schools represent additional opportunities. Practitioner points: Over and above any inherited risk, a range of family interactional factors are strongly associated with self‐harming behaviours in young people Therapy has the potential to make a positive difference by focusing on enhancing family cohesion and adaptability, whilst reducing discord and violence. Discussions that enhance perceived parental support and warmth may be particularly helpful Therapists should attend to issues of perceived difference and potential victimization (bullying, gender orientation and identity, ethnic minority status) as these may play an important role in self‐harm